THE IMPACT OF DEMOGRAPHICS ON UMRAH PILGRIMS' SATISFACTION WITH PRIVATE TRAVEL AND TOUR COMPANIES IN MELAKA TENGAH - Faridah Bt Che In; Noranis Hazwani Binti Azmi; Nur Diyanah Binti Ali (Jurnal Penyelidikan Sains Sosial, 2023)
One of the most crucial elements for corporate success is customer happiness. Client happiness leads to customer loyalty, which in turn aids the organization's performance in terms of sales and profit. Customer happiness must be prioritized in order to ensure business excellence in the face of fierce competition among businesses. This paper is about a study on the impact of Umrah Pilgrims' demographics on customer satisfaction. A questionnaire was produced and distributed to 200 respondents from a Melaka Tengah-based private travel and tour firm. This study uses correlation, ANOVA and T-Test method to analyses the findings. SPSS 18 software was used to examine relationships and effect of demographic on Umrah Pilgrims' Satisfaction. Overall, the descriptive result demonstrates a high degree of customer satisfaction, indicating that customers are pleased with the packages supplied by a Melaka Tengah-based private travel and tour company. This finding stated, demographics are a key component that private trips and tours companies in Melaka Tengah and should emphasize in order to provide the greatest quality service for client satisfaction. According to results, the higher perceived value leads to higher customer satisfaction. Therefore, the tour and travel company managers should take into consideration that clients who are coming to company expect to have medium or high quality of service and they expect safe journey of tours. As a result, this data clearly indicates the importance of demographic factors in ensuring consumer satisfaction.